Borderline anaemia and postoperative outcome in women undergoing major abdominal surgery: a retrospective cohort study. (16th October 2019) - Miles, L. F.; Larsen, T.; Bailey, M. J.; Burbury, K. L.; Story, D. A.; Bellomo, R.
Summary: Pre‐operative anaemia is typically diagnosed with a haemoglobin concentration < 120 g.l −1 for women and < 130 g.l −1 for men on the basis of limited evidence. This retrospective cohort study stratified women undergoing elective, major abdominal surgery based on pre‐operative haemoglobin concentration: anaemic (< 120 g.l −1 ); borderline anaemic (120–129 g.l −1 ); and non‐anaemic (> 130 g.l −1 ). Data from 1554 women were analysed. Women with borderline anaemia had a greater incidence of postoperative complications (55 (16%) vs. 110 (11%); p = 0.026), longer duration of hospital stay (median (IQR [range]) 3 (1–6 [0–69]) days vs. 2 (1–5 [0–80]) days; p = 0.017) and fewer days alive and out of hospital at postoperative day 30 (median (IQR [range]) 27 (23–29 [0–30]) vs. 28 (25–29 [0–30]) days; p = 0.017) compared with non‐anaemic women. However, after matched cohort analysis, these outcome differences no longer remained statistically significant. After multivariable adjustment for procedure, Charlson comorbidity index and patient age, a negative relationship between logarithmic pre‐operative haemoglobin concentration and duration of stay was found (parameter estimate (standard error) −0.006 (0.003) vs. 0.003 (0.003) for a haemoglobin concentration < 130 g.l −1 vs. > 130 g.l −1, respectively; p = 0.03); the difference in duration of stay was approximately 50% greater for women with a haemoglobin concentration of 120 g.l −1 compared with those with a haemoglobin concentration of 130 g.l −1 . Although the contribution of borderline anaemia to the incidence of postoperative complications is uncertain, the current diagnostic criteria should be re‐assessed.